Alcohol Consumption and Perceptions of Health Risks During COVID-19: A Qualitative Study of Middle-Aged Women in South Australia - Lunnay, Belinda; Foley, Kristen; Meyer, Samantha B.; Warin, Megan; Wilson, Carlene; Olver, Ian; Miller, Emma R.; Thomas, Jessica; Ward, Paul R. (Frontiers in Public Health, 2021)
Australian women’s alcohol consumption has increased in frequency during COVID-19. Research suggests this is to cope with stress resulting from the pandemic and COVID-19 countermeasures that require social distancing. This is a critical public health concern because increased alcohol consumption, even for a short period, increases the myriad longer-term health risks associated with cumulative exposure to alcohol. This paper provides unique qualitative evidence of how health risk perceptions are re-focused toward the shorter-term during the pandemic, through analysis of interviews with 40 middle-aged Australian women (aged 45-64) representing a range of self-perceived drinking status’ (‘occasional’ / ‘light’ / ‘moderate’ / ‘heavy’) before and then during the pandemic (n=80 interviews). Our analysis captures women’s risk horizons drifting away from the uncertain longer-term during COVID-19, toward the immediate need to ‘get through’ the pandemic. We show how COVID-19 has increased the perceived value of consuming alcohol among women, particularly when weighed up against the social and emotional ‘costs’ of reducing consumption. Our findings have implications for the delivery of alcohol-related health risk messages designed for middle-aged women both during, and into the recovery phases of the pandemic, who already consume more alcohol and experience more alcohol-related health risk than women in other age groups.